Exploring the Role of English as a Foreign Language Receptive Skills and Learning Strategy Usage in the Ability to Acquire and Apply Knowledge at the Beginning of Higher Education - Magyar, Andrea; Habók, Anita; Molnár, Gyöngyvér (Frontiers in Psychology, 2022)
Foreign language learning plays a prominent role in the world today not only for communication across borders, but also for the potential benefits of other learning skills. The main objective of this research is to examine and explore the relationship between first-year full-time undergraduate students’ (N = 1,257) English as a foreign language (EFL) reading and listening achievement and learning strategy preferences in relation to knowledge acquisition and knowledge application. Our results show that students achieved significantly better on listening tasks than on reading tasks and that their knowledge acquisition performance was higher than their knowledge application achievement. The majority of the participants reported that they usually or always employ learning strategies, with the most preferred strategy type being the control strategy. The structural model shows that language learning, and knowledge acquisition and application are strongly interrelated; moreover, the level of use of memorization and elaboration strategies directly affects both knowledge acquisition and application skills. This suggests that EFL learning significantly influences the development of knowledge acquisition and knowledge application, which are essential in a range of areas in education and society today.